PERBANDINGAN ALGORITMA HORSPOOL DAN ALGORITMA RAITA PADA APLIKASI ISTILAH PSIKOLOGI BERBASIS ANDROID - Mamta Culkari Puding; Jumadil Nangi; Adha Mashur Sajiah (Informatics Engineering Department of Halu Oleo University, 2019)
The lack of professional health personnel in Indonesia has resulted in many people with mental disorders who have not been treated medically. To make it easier for the mental health workers, especially psychology students to study the term in psychology. It is necessary to have a digital dictionary because a tick printed book dictionary makes it difficult to carry around and the search term desired requires a long time. Based on this, a dictionary application for the psychology term based on Android was made.To make this application implemented the string matching method on the codeword search. String matching has several algorithms, some of which are Horspool algorithm and Raita algorithm.In this research study an analysis of the comparison between the Horspool algorithm and Raita algorithm, to determine the most useful algorithms in the dictionary of psychological terms. The parameter used to compare the two algorithms search time (ms) and complexity algorithms (Big-O).The results of this study show that Raita Algorithm has a faster search than Horspool Algorithm and the complexity of Raita algorithm has faster than Horspool algorithm. The average total velocity of time for Raita algorithm is 13,60 ms and Horspool algorithm are 14,79 ms. The complexity of Raita algorithm is T(n) = Ɵ(MN) and the complexity of Horspool algorithm is T(n) = Ɵ(M(N-2)).Keywords—Dictionary, Psychology, String Matching, Horspool Algorithm, Raita AlgorithmDOI : 10.5281/zenodo.3242287